Protection of Heirs Against Absentee Land Ownership - Retno Sariwati; Selvia Wisuda (Faculty of Law, University of Merdeka Malang, 2023)
Land ownership is often non-existent in communities. Ownership through the process of inheritance, where the heirs live outside the district area where the object of inheritance is located. For example, a person living in a city inherits from his parents a farm in the village; this automatically made the heirs the absentee landowners. This study aims to provide legal protection for absentee land ownership obtained from the inheritance process. This study uses normative legal research methods with several approaches, namely the statutory approach and the conceptual approach. Legal protection for heirs of owners of land rights that do not exist in positive law. If the heirs do not exploit or utilize land that does not exist as mandated by law adequately, then there is no legal protection for the heirs. The prohibition of absentee land does not apply to persons or legal entities residing outside the sub-district which borders the location of agricultural land and allows agricultural land owners to cultivate or cultivate it efficiently.How to cite item: Sariwati, Retno, and Selvia Wisuda. â€œProtection of Heirs Against Absentee Land Ownership.â€ Jurnal Cakrawala Hukum. 14 no. 1 (2023): 46-53. DOI: 10.26905/idjch.v14i1.10006.